Insights into the Stability of Graphene Oxide Aqueous Dispersions - Codrut Costinas; Catalin Alexandru Salagean; Liviu Cosmin Cotet; Monica Baia; Milica Todea; Klara Magyari; Lucian Baia (Nanomaterials, 2022)
Understanding graphene oxide’s stability (or lack thereof) in liquid solvents is critical for fine-tuning the material’s characteristics and its potential involvement in future applications. In this work, through the use of structural and surface investigations, the alteration of the structural and edge-surface properties of 2D graphene oxide nanosheets was monitored over a period of eight weeks by involving DLS, zeta potential, XRD, XPS, Raman and FT-IR spectroscopy techniques. The samples were synthesized as an aqueous suspension by an original modified Marcano-Tour method centred on the sono-chemical exfoliation of graphite. Based on the acquired experimental results and the available literature, a phenomenological explanation of the two underlying mechanisms responsible for the meta-stability of graphene oxide aqueous dispersions is proposed. It is based on the cleavage of the carbon bonds in the first 3–4 weeks, while the bonding of oxygen functional groups on the carbon lattice occurs, and the transformation of epoxide and hydroxyl groups into adsorbed water molecules in a process driven by the availability of hydrogen in graphene oxide nanosheets.